Thoracic Endovascular Aortic Repair for Aberrant Subclavian Artery and Stanford Type B Aortic Intramural Hematoma - Xu, Xia; Wang, Daoquan; Hou, Ningxin; Zhou, Hongmin; Li, Jun; Tian, Liang (Frontiers in Surgery, 2022)
Objectives To evaluate the in-hospital and later outcomes of thoracic endovascular aortic repair (TEVAR) for type B intramural hematoma (TBIMH) combined with an aberrant subclavian artery (aSCA). Methods In the period from January 2014 to December 2020, 12 patients diagnosed with TBIMH combined with aSCA and treated by TEVAR were enrolled in this retrospective cohort study, including 11 patients with the aberrant right subclavian artery (ARSA) and 1 with an aberrant left subclavian artery (ALSA). A handmade fenestrated stent-graft or chimney stent or hybrid repair was performed when the proximal landing zone was not enough. Results The mean age of all the patients was 59.2 ± 7.6 years, and 66.7% of patients were men. There were 4 patients with Kommerell's diverticulum (KD). The procedures in all 12 patients were technically successful. There was one case each of postoperative delirium, renal impairment, and type IV endoleak after TEVAR. During follow-up, 1 patient died of acute pancreatitis 7 months after TEVAR. The overall survival at 1, 3, and 5 years for the patients was 90.9, 90.9, and 90.9%, respectively. KD was excluded in 2 patients, and the handmade fenestrated stent-graft was applied in the other 2 patients to preserve the blood flow of the aSCA. No neurological complications developed and no progression of KD was observed during the follow-up. Conclusion Thoracic endovascular aortic repair for patients with aSCA and TBIMH is promising. When KD was combined, we could exclude KD or preserve the blood flow of aSCA with regular follow-up for the diverticulum according to the size of the KD.